3D geophysical imaging for site-specific characterization plan of an old landfill. (June 2018) - Di Maio, R.; Fais, S.; Ligas, P.; Piegari, E.; Raga, R.; Cossu, R.
Abstract: As it is well-known, the characterization plan of an old landfill site is the first stage of the project for the treatment and reclamation of contaminated lands. It is a preliminary in-situ study, with collection of data related to pollution phenomena, and is aimed at defining the physical properties and the geometry of fill materials as well as the possible migration paths of pollutants to the surrounding environmental targets (subsoil and groundwater). To properly evaluate the extent and potential for subsoil contamination, waste volume and possible leachate emissions from the landfill have to be assessed. In such perspective, the integrated use of geophysical methods is an important tool as it allows a detailed 3D representation of the whole system, i.e. waste body and hosting environment (surrounding rocks). This paper presents a very accurate physical and structural characterization of an old landfill and encasing rocks obtained by an integrated analysis of data coming from a multi-methodological geophysical exploration. Moreover, drillings were carried out for waste sampling and characterization of the landfill body, as well as for calibration of the geophysical modeling.